HUBUNGAN KETERAMPILAN BERHITUNG DAN PERSEPSI SISWA DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD SE-KECAMATAN KARANGPUCUNG CILACAP - Rina Meida Hafitriana; A. A. Sujadi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Abstract: The purpose of this research is to find out the correlation between numeracy skill and students perception on mathematics with the results of mathematics learning. This research method applied descriptive of correlation. The population in this research is grade IV Elementary School in subdistric Karangpucung Cilacap, with a sample of 6 schools taken by cluster random sampling. Analytical techniques multiple regression analysis with requirment of normality, linierit, and Multicolinierity. Based on the results of the research, R = 0,710, meaning that there was a positive correlation between numeracy skill and students perception on mathematics with the results of mathematics learning. 0,599, meaning that there was a positive correlation between numeracy skill with the results of mathematics learning. 0,258, meaning that there was a positive correlation between students perception on mathematics with the results of mathematics learning.Â